The Defect in the Hurler and Scheie Syndromes: Deficiency of α-L-Iduronidase - Bach, Gideon (1972)
Skin fibroblasts cultured from patients affected with the Hurler or Scheie syndromes (mucopoly-saccharidoses I or V, respectively) have a functional deficiency of a protein required for catabolism of sulfated mucopolysaccharide that has been designated the “Hurler corrective factor.” We now show Hurler factor purified from normal human urine to be associated with α-L-iduronidase activity. Cell lines deficient in Hurler corrective factor have no detectable activity of α-L-iduronidase (less than 3% of that found in cells from individuals of other genotypes). Such correspondence indicates that Hurler corrective factor and α-L-iduronidase are the same entity. Correction of deficient cells is accompanied by an efficient uptake of α-L-iduronidase from the medium.